A linguagem verbal de videogames em uma perspectiva multidimensional e de Ciência Aberta - Escarabelin, Lucas Ferraz (2024)
Video games are a recent form of digital media which has been gaining popularity over the years. This form of media addresses different themes and shows different discourses, therefore, understanding video games is, in a way, a method of understanding contemporary times. With this idea in mind, a corpus was collected for this research consisting of English dialogues from characters originated from 60 video games from 4 popular genres, namely RPG, Action & Adventure, Survival Horror and Shooters. Furthermore, all characters in the corpus were classified, with help from Artificial Intelligence, as “good guys”, “bad guys” and “neutral” in order to understand whether these roles influenced the types of speech used by the characters. The theorical foundation of this research is based on three aspects: Corpus Linguistics, Game Theory and Open Science. In relation to Corpus Linguistics, the main contribution to this research comes from Multidimensional Analysis (BIBER, 1988; BERBER SARDINHA; VEIRANO PINTO, 2014; 2019), and Lexical Multidimensional Analysis (BERBER SARDINHA, 2019, 2020), focused at identifying the discourses present in the study corpus formed by video games and to understand the way violence manifests itself in this media. The second theoretical contribution corresponds to Game Theory, which was used to critically understand what roles video games play in society. Specifically, this theory was used to assist in the interpretation of the results found by the Lexical Multidimensional Analysis. The third theoretical contribution comes from Open Science considering that this research is part of the institutional proposal of the ‘Multimodal/multilingual Portal for the advancement of open science in the Humanities’ promoted by CNPq. This research contributes to the portal by sharing the information collected and results found during the research process, as well as behind-the-scenes information about the entire research. In addition to the objectives mentioned above, there is also the goal of clarifying public opinion about video games, which have been often seen negatively by the public, and, also striving to encourage the acceptance of this form of media by the linguistic scientific community by demonstrating the amount of unexplored content for future research